Fractional exhaled NO and serum pneumoproteins after swimming in a chlorinated pool - Carbonnelle, S.; Bernard, A.; Doyle, I. R.; Grutters, J.; Francaux, M. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The purpose of this study was to examine whether a swimming session performed in a pool sanitized with chlorine-based agents induces lung inflammation, modifies lung epithelium permeability, and alters lung function.